2022
DOI: 10.1007/s12325-022-02081-w
|View full text |Cite
|
Sign up to set email alerts
|

Superior Bioavailability of a Novel Curcumin Formulation in Healthy Humans Under Fasting Conditions

Abstract: Background: Despite its broad range of biological activities, use of curcumin is limited because of poor bioavailability. Here we report a novel curcumin formulation, Curcuwin Ultra? (CU?), with superior bioavailability as compared to 95% turmeric extract (TUR 1800). Methods: A randomized, double-blind, threetreatment, crossover oral bioavailability study was conducted in 24 healthy volunteers under fasting conditions. Subjects received a single dose of CU? 250 mg, 500 mg and 1900 mg of TUR1800 as per randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…In another study, curcuRouge was demonstrated to reduce the neutrophil to lymphocyte ratio without any safety issues in healthy subjects . Another formulation Curcuwin Ultra+ showed enhanced bioavailability and was found to be safe in healthy subjects . Another next-generation formulation with superior bioavailability, Longvida was also elucidated to reduce fatigue, and oxidative stress, tension, and anxiety, and improved mood-related issues, and cognitive functions in healthy individuals with excellent safety and no side effects. Moreover, clinical trials on obese patients have revealed that Longvida intake improved cerebral artery stiffness, cerebrovascular responsiveness, and lipid profile without side effects. It has also been shown to be beneficial in treating both OSF and osteoarthritis. , Another illuminating clinical trial evidenced the use of Longvida in detecting amyloid spots in the retina of Alzheimer’s patients and reported that this formulation exhibits a greater capacity to identify these spots in positron emission tomography (PET) scanning compared to conventional amyloid PET in longitudinal evaluation of amyloid risk and neurodegeneration (LEARN) study …”
Section: Curcumin Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, curcuRouge was demonstrated to reduce the neutrophil to lymphocyte ratio without any safety issues in healthy subjects . Another formulation Curcuwin Ultra+ showed enhanced bioavailability and was found to be safe in healthy subjects . Another next-generation formulation with superior bioavailability, Longvida was also elucidated to reduce fatigue, and oxidative stress, tension, and anxiety, and improved mood-related issues, and cognitive functions in healthy individuals with excellent safety and no side effects. Moreover, clinical trials on obese patients have revealed that Longvida intake improved cerebral artery stiffness, cerebrovascular responsiveness, and lipid profile without side effects. It has also been shown to be beneficial in treating both OSF and osteoarthritis. , Another illuminating clinical trial evidenced the use of Longvida in detecting amyloid spots in the retina of Alzheimer’s patients and reported that this formulation exhibits a greater capacity to identify these spots in positron emission tomography (PET) scanning compared to conventional amyloid PET in longitudinal evaluation of amyloid risk and neurodegeneration (LEARN) study …”
Section: Curcumin Formulationsmentioning
confidence: 99%
“… 303 Another formulation Curcuwin Ultra+ showed enhanced bioavailability and was found to be safe in healthy subjects. 304 Another next-generation formulation with superior bioavailability, Longvida was also elucidated to reduce fatigue, and oxidative stress, tension, and anxiety, and improved mood-related issues, and cognitive functions in healthy individuals with excellent safety and no side effects. 305 308 Moreover, clinical trials on obese patients have revealed that Longvida intake improved cerebral artery stiffness, cerebrovascular responsiveness, and lipid profile without side effects.…”
Section: Curcumin Formulationsmentioning
confidence: 99%
“…In fertile women with regular menstrual cycles, encapsulated curcumin reduced the endometrial expression of VEGF ( p < 0.05) and enhanced COX-2 expression ( p > 0.05) compared to the placebo group . Kothapally et al showed that a novel curcumin formulation (curcumin ultra+) possessed enhanced bioavailability and reduced safety issues at 250 and 500 mg doses (single) compared to 1000 mg turmeric extract in healthy volunteers under fasting conditions . Loriczova et al demonstrated that iron (18 mg and 65 mg) supplementation along with curcumin (500 mg) reduces iron-induced systemic inflammation by reducing plasma levels of TNF-α and thiobarbituric acid-reactive substances in healthy individuals compared to those who received a placebo .…”
Section: Clinical Trials Of Turmeric and Curcuminmentioning
confidence: 99%
“…Furthermore, Curcuwin Ultra+ (CU+), a novel formulation designed to protect curcuminoids from intestinal degradation, demonstrated a significant higher total systemic exposure and C max for total curcuminoids compared with 95% turmeric extract (TUR 1800). Besides CU+ was 40% faster absorbed, it possesses superior bioavailability even at lower concentrations (250 and 500 mg) in comparison with higher doses of TUR 1800 (1900 mg) in healthy volunteers under fasting conditions [ 30 ]. The water-dispersible turmeric extract containing 60% curcuminoids (TurmXtra 60N), referred to as WDTE60N, using a concentration of 150 mg of curcuminoids, demonstrated a higher absorption and exposure for free curcumin, total curcumin, and total curcuminoids at 10-fold lower dose than standard turmeric extract 95% (STE95) (1500 mg) [ 31 ].…”
Section: Curcuminmentioning
confidence: 99%